The immune-metabolic crosstalk between CD3+C1q+TAM and CD8+T cells associated with relapse-free survival in HCC - Yang, Yanying; Sun, Lu; Chen, Zhouyi; Liu, Weiren; Xu, Qiyue; Liu, Fangming; Ma, Mingyue; Chen, Yuwen; Lu, Yan; Fang, Hao; Chen, Geng; Shi, Yinghong; et al. (Frontiers in Immunology, 2023)
Improving the understanding of the HCC immune microenvironment is critical for integrating novel treatment strategies to increase the anti-tumor response. We collected scRNA-Seq information from paired tumor and peri-tumor tissues of HCC to reveal the CD3+cells composition and differentiation trajectories. Among them, we found that a previously unreported population, CD3+C1q+TAM, was positively linked to a better survival prognosis. By calculating the interaction scores between clusters, we found that CD3+C1q+TAM significantly interacted with CD8+CCL4+T cells. Compared to the peri-tumor tissue, their interaction was attenuated in tumors. The dynamic presence of CD3+C1q+macrophages has also been verified in the peripheral blood of patients with sepsis. Furthermore, we found that CD3+C1q+TAM affected T cell immunity through C1q signaling-induced metabolic and epigenetic reprogramming, thereby potentially affecting tumor prognosis. The data reveals the interaction between C1q and the metabolism of CD8+T cells and provides implications for regulating the immunosuppressive tumor microenvironment.